2000
DOI: 10.1055/s-2000-6352
|View full text |Cite
|
Sign up to set email alerts
|

Organophosphorus Compounds, Part 149. Preparation of 1,3-Oxaphospholes by Transition Metal-Catalyzed Reactions of α-Diazo-β-dicarbonyl Compounds with tert-Butylphosphaacetylene

Abstract: In the presence of Rh 2 (OAc) 4 as catalyst the cyclic a-diazo-b-dicarbonyl compounds 7a-c react with tert-butylphosphaacetylene 2 under elimination of nitrogen to furnish the 1,3-oxaphosphole derivatives 8a-c. The feasible competing reaction with formation of the 1,2,4-diazaphospholes 9a-c has not been observed.The class of the 1,3-oxaphospholes still constitutes a relatively unknown area in the fertile field of heterophosphole chemistry. 2 Currently, only two separate routes to nonbenzo-condensed 1,3-oxaphos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…The angle on the phosphorus atom is comparable to another four‐membered ring with a CP bond (C‐P‐C 76.9(1)°) 21. The t Bu group on the carbon atom is bent toward the oxygen atom and thus away from the phosphorus atom (C17‐C16‐P1: 130.5(2) and 131.1(2)° vs. C17‐C16‐O1: 115.6(2) and 115.2(2)°), which was previously observed for another PCO heterocycle (C‐C‐P: 131.75(14)° vs. C‐C‐O: 113.4(2)°) 20a…”
Section: Resultssupporting
confidence: 70%
“…The angle on the phosphorus atom is comparable to another four‐membered ring with a CP bond (C‐P‐C 76.9(1)°) 21. The t Bu group on the carbon atom is bent toward the oxygen atom and thus away from the phosphorus atom (C17‐C16‐P1: 130.5(2) and 131.1(2)° vs. C17‐C16‐O1: 115.6(2) and 115.2(2)°), which was previously observed for another PCO heterocycle (C‐C‐P: 131.75(14)° vs. C‐C‐O: 113.4(2)°) 20a…”
Section: Resultssupporting
confidence: 70%
“…In contrast, other heterophospholes, such as 1,3‐thiaphospholes are thought to be aromatic; however, recent calculations also indicate that the HOMO in these compounds is mainly located on the P=C fragment . In the solid‐state structures of some 1,3‐oxaphospholes, enhanced aromaticity is anticipated from the observed P=C bond length, which falls in between a typical single and double bond . These theoretical and experimental findings clearly show that the bonding situation in phospholes largely depends on several factors, such as their substituents, enforced planarity, and other electronic factors.…”
Section: Cyclic Structures Containing Phosphorus and Other Heteroelemmentioning
confidence: 77%
“…[32] In the solid-state structures of some 1,3-oxaphospholes,e nhanced aromaticity is anticipated from the observed P=Cb ond length, which falls in between at ypical single and double bond. [33] Theset heoretical and experimental findings clearly show that the bonding situation in phospholes largely depends on severalf actors, such as their substituents,e nforced planarity,a nd other electronic factors. Moreover the introduction of additional heteroelements can lead to drastic alterations of the parent system.…”
Section: Aromaticity In Phospholesmentioning
confidence: 97%
“…534 Interestingly, Regitz showed that the Rh(II)-catalyzed reaction of α-diazocarbonyl compounds with tert -buthylphosphaacetylene furnishes 1,3-oxaphospholes. 535 …”
Section: Synthesis Of 5-membered Heterocycles With Two or More Hetmentioning
confidence: 99%